Current PI-Gain Determination for Permanent Magnet Synchronous Motor by using Particle Swarm Optimization - Ahmad Asri Abd Samat; M.S Zainal; L.N Ismail; Wan Salha Saidon; A. Idzwan Tajudin (Institute of Advanced Engineering and Science, 2017)
This paper proposes the modern approach using Particle Swarm Optimization (PSO) algorithm in determining the ideal value of Proportional Integral (PI) gain for current controller of Permanent Magnet Synchronous Motor (PMSM). Controlling the torque of PMSM and optimizing the PI-gain are the main objectives of this project. The PI controller is employed to control the speed and the torque of the PMSM with the implementation of Field Oriented Control (FOC) method. This new proposed PSO technique proved that the ability in reducing the torque ripple compared to conventional heuristic method. The ideal PI-gain acquired from the PSO was included into current PI controller. From the result obtained, it shows that the viability of the PSO technique is the best to determine PI-gain for current controller.